Template-free pseudomorphic synthesis of tungsten carbide nanorods - Yan, Ya (2013)
A unique nanorod-structured tungsten carbide material with high specific surface area of 198 m2 g−1 is successfully synthesized for the first time by pseudomorphic transformation of chemically synthesized WO3 nanorods through a high-temperature method. An electrocatalyst composed of Pt nanoparticles supported on WC nanorods demonstrates higher electrocatalytic activity for methanol electro-oxidation, better tolerance to CO poisoning, and superior performance for cathodic electrocatalytic hydrogen evolution than a Pt/C catalyst. This work provides a novel method to synthesize high-surface-area nanorod-structured WC materials by preparing oxide precursors with the desired external morphology, thus offering great potential for a broad range of applications of these materials in related reaction systems.